Effect of Elicitors on Morpho-Physiological Performance and Metabolites Enrichment in Valeriana jatamansi Cultivated Under Aeroponic Conditions - Partap, Mahinder; Kumar, Pankaj; Kumar, Anil; Joshi, Robin; Kumar, Dinesh; Warghat, Ashish R. (Frontiers in Plant Science, 2020)
The use of new agricultural technologies such as soilless and aeroponic cultivation systems is a valuable approach to medicinal plant production. The present study investigated the prospects of enhancing yield and secondary metabolite production in Valeriana jatamansi under aeroponic cultivation using elicitors, such as yeast extract and methyl jasmonate. Plants were evaluated by measuring growth parameters, photosynthetic rate, and secondary metabolites contents (on dry weight basis). Maximum plant height (36.83 cm), leaf number (17.67), rootlet number (37.33), and rootlet length (6.90 cm) were observed at 0.5 mg/L yeast extract treatment; whereas treatment levels of 1.5 mg/L yeast, extract and 150 µM methyl jasmonate resulted in maximum leaf length (6.95 cm) and leaf width (5.43 cm), respectively. Maximum photosynthetic rate (5.4053 µmol m-2s-1) and stomatal conductance (0.0656 mmol m-2s-1) were recorded at treatment levels of 0.5 mg/L and 1.5 mg/L yeast extract respectively, whereas at 150 µM methyl jasmonate treatment, transpiration rate was 0.9046 mmol m-2s-1. In aeroponic cultivation, the maximum content of valerenic acid and hydroxy valerenic acid was detected in leaf (2.47 and 8.37 mg/g) and root (1.78 and 7.89 mg/g) at treatment levels of 100 µM and 150 µM methyl jasmonate, respectively. Acetoxy valerenic acid was highest in leaf (1.02 mg/g) at 1.5 mg/L yeast extract, and in the root (2.38 mg/g) at 150 µM methyl jasmonate. Gas chromatography-mass spectrometry analysis, identified twenty-eight volatile compounds in roots, of which three isovaleric acid (6.72-50.81%), patchouli alcohol (13.48-25.31%) and baldrinal (0.74-25.26%) were the major constituents. The results revealed that, besides roots, leaves could also be utilized as a prominent alternative source for targeted secondary metabolites. In conclusion, aeroponic cultivation offers year-round quality biomass production and ease to access subsequent roots harvest in V. jatamansi, to meet the demand of the pharmaceutical industries.